Experimental and numerical investigations into molten-pool sloshing motion for severe accident analysis of sodium-cooled fast reactors: A review - Xu, Ruicong; Cheng, Songbai (Frontiers in Energy Research, 2022)
Safety issues are especially crucial to Sodium-cooled Fast Reactor (SFR). Owing to the SFR safety analysis over the past years, a specific type of sloshing motion was substantiated to probably occur during the Core Disruptive Accidents (CDAs) of SFR in the molten pool due to local neutronic power excursion or pressure developments, thereby significantly influencing the recriticality. Recognizing its notable importance in improving the evaluation of CDA of SFR, extensive valuable knowledge about this phenomenon was garnered over the past decades based on some experimental studies on its thermal-hydraulic mechanism and characteristics. Based on these studies, simulations using various numerical approaches, such as SIMMER code, finite volume particle method and smoothed particle hydrodynamic method, were attempted to reproduce the sloshing motion under various experimental conditions for verifying their reasonability and applicability, thereby promoting the development of SFR safety analysis. Aimed to provide useful references for the future SFR safety analyses and assessments, the past experimental and numerical investigations on the thermal-hydraulics aspect of molten-pool sloshing motion are systematically reviewed and summarized in this paper. In addition, to enhance deeper and more comprehensive research for the sloshing motion, some future prospects are also discussed. Knowledge from the experimental and numerical investigations on the molten-pool sloshing motion is supposed to be valuable for not only the improvement and verifications of SFR safety analysis codes but also for providing reference to the studies of sloshing motion in other engineering fields.